Rural youth in southern Nigeria: fractured lives and ambitious futures - Crossouard, B.; Dunne, M.; Szyp, C.; Madu, Tessy; Teeken, Béla (SAGE Publications, 2022)
This article draws on recent research (2017–20) into the livelihoods and imagined futures of rural youth in four communities in southern Nigeria. The research involved observations, sex-segregated focus group discussions and individual interviews. Taking up insights from sociologists of education and work, our analysis shows how rural youth simultaneously navigated schooling, farming, low-paid vocational work and family obligations in ways that were highly gendered. We show the gulf between youth’s daily lives and their imagined futures, and how their desires for better lives, whether through ‘white-collar’ work or expanded farming activities, often involved moving to more ‘civilised’ or ‘developed’ contexts. Commitment to family nevertheless ran through youth’s narratives, in ways that reflected a deeply gendered, sexual economy. We conclude by highlighting the relevance of a connected sociology that embraces postcolonial and feminist scholarship to advance future studies of rural youth, gender and work in the Global South.